Working With Them: Small-Scale Landlord Strategies for Avoiding Evictions. Issue 3 (3rd September 2021) - Balzarini, John; Boyd, Melody L.
ABSTRACT: This study draws on 71 indepth, semistructured interviews with landlords and property managers in Philadelphia, Pennsylvania. We find that the perceived burdens associated with evictions often make evictions less desirable for small-scale landlords than finding ways to work with tenants to keep them in their homes, including developing payment plans to help tenants catch up on back rent, adjusting rental rates, accepting services in lieu of rent, and aiding in referrals to housing and social service programs. Some landlords employ a technique of paying tenants to vacate, a practice referred to as cash for keys, which is an informal, off-the-books eviction. Our findings suggest that off-the-books evictions are far more prevalent than has been measured in official eviction data; therefore, the prevalence of residential displacement is more severe than previously documented.